Unveiling the Antifouling Performance of Different Marine Surfaces and Their Effect on the Development and Structure of Cyanobacterial Biofilms - Faria, Sara I.; Teixeira-Santos, Rita; Romeu, Maria J.; Morais, João; Jong, Ed de; Sjollema, Jelmer; Vasconcelos, Vítor; Mergulhão, Filipe J. (Microorganisms (Basel), 2021)
Since biofilm formation by microfoulers significantly contributes to the fouling process, it is important to evaluate the performance of marine surfaces to prevent biofilm formation, as well as understand their interactions with microfoulers and how these affect biofilm development and structure. In this study, the long-term performance of five surface materials—glass, perspex, polystyrene, epoxy-coated glass, and a silicone hydrogel coating—in inhibiting biofilm formation by cyanobacteria was evaluated. For this purpose, cyanobacterial biofilms were developed under controlled hydrodynamic conditions typically found in marine environments, and the biofilm cell number, wet weight, chlorophyll a content, and biofilm thickness and structure were assessed after 49 days. In order to obtain more insight into the effect of surface properties on biofilm formation, they were characterized concerning their hydrophobicity and roughness. Results demonstrated that silicone hydrogel surfaces were effective in inhibiting cyanobacterial biofilm formation. In fact, biofilms formed on these surfaces showed a lower number of biofilm cells, chlorophyll a content, biofilm thickness, and percentage and size of biofilm empty spaces compared to remaining surfaces. Additionally, our results demonstrated that the surface properties, together with the features of the fouling microorganisms, have a considerable impact on marine biofouling potential.